Pengaruh Angka Harapan Hidup dan Pertumbuhan Ekonomi terhadap IPM di ASEAN - Dewi, Alviana; Setianingrum, Helvy Fatima (Universitas Negeri Surabaya, 2024)
The welfare of society, represented by human development, is influenced by various factors, primarily health and economic conditions. This study examines the effect of life expectancy (LE) and economic growth on the Human Development Index (HDI) in ASEAN during the 2012–2021 period. The data were sourced from the Asian Development Bank (ADB) website. Panel data regression analysis was employed in this research. The findings indicate that LE has a partially significant positive effect on HDI, while the economic growth variable has a partially significant negative effect on HDI. Both LE and economic growth variables jointly have a significant effect on HDI. The coefficient of determination reveals that 86.60% of the variations in HDI can be explained by the independent variables, while the remaining 13.40% is influenced by other factors outside the scope of this study.